2019
DOI: 10.1002/jsfa.9996
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecules extraction from coffee and cocoa by‐ and co‐products using deep eutectic solvents

Abstract: BACKGROUND: Coffee pulp (CP), cocoa husk (CH), and pod husk (CPH) are the main agro-residues from coffee and cocoa industries. They are sources of useful biomolecules, such as phenolic compounds, fibers, and alkaloids, among others. In this study, different compositions of deep eutectic solvents (DES) were investigated as a green and sustainable extraction media, with respect to their extraction capacity. The extraction yields were evaluated using heat stirring-assisted extraction (HSE) or ultrasound-probe ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 55 publications
0
28
0
2
Order By: Relevance
“…In the case of extraction of phenolic acids by the UAE-DES/NADES methods, most authors have found choline chloride:lactic acid-based DES (molar ratio usually 1:2) as the most promising solvent [103][104][105]. The combination of choline chloride with other organic acids such as: p-toluenesulfonic acid [66], oxalic acid [106] and citric acid [107] is also interesting.…”
Section: Ultrasound-assisted Des/nades Extractions Of Bioactive Compomentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of extraction of phenolic acids by the UAE-DES/NADES methods, most authors have found choline chloride:lactic acid-based DES (molar ratio usually 1:2) as the most promising solvent [103][104][105]. The combination of choline chloride with other organic acids such as: p-toluenesulfonic acid [66], oxalic acid [106] and citric acid [107] is also interesting.…”
Section: Ultrasound-assisted Des/nades Extractions Of Bioactive Compomentioning
confidence: 99%
“… Sugar-based NADES have the highest viscosity, which makes them difficult to handle and consequently limits their use in the commercial extraction processes [ 82 ]. Choline chloride:organic acid-based DES/NADES in combination with UAE is the most effective extraction methodology described for the isolation of phenolic acids from the various plant matrices [ 66 , 105 , 106 , 107 , 126 ]. In the case of the flavonoid class, the results presented in the majority of the papers have identified choline chloride:polyalchol-based DES/NADES as the most promising solvents ( Table 1 and Table 2 ).…”
Section: Conclusion With Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…NaDES are stable eutectic mixtures composed of a hydrogen bond acceptor (HBA) and a hydrogen bond donor (HBD). Recently, Ruesgas-Ramón et al [ 62 ] tested six different DES using heat-stirring assisted extraction (1 h, 60 °C) to extract CGAs from coffee and cocoa by-products. The extraction yield was compared with the results obtained in the same experimental conditions using 70% ethanol.…”
Section: Conventional Extraction Methodsmentioning
confidence: 99%
“…Major flavonoids were identified as quercetin, kaempferol, and myricetin. Very recently, Ruesgas-Ramón et al [105] used agro-residues from coffee and cocoa industries to recover biomolecules using DESs. The authors reported that the use of lactic acid-ChCl (2:1) provided higher phenolics extraction with ultrasound-probe-assisted extraction than heat stirring-assisted extraction.…”
Section: Extraction and Recovery Of Flavonoids From Agro-industrial Lignocellulosic Wastesmentioning
confidence: 99%